Raising the Dead? Limits of CPR and Harms of Defensive Practices - Skowronski, George (The Hastings Center report, 2022)
We describe the case of an eighty-four-year-old man with disseminated lung cancer who had been receiving palliative care in the hospital and was found by nursing staff unresponsive, with clinically obvious signs of death, including rigor mortis. Because there was no documentation to the contrary, the nurses commenced cardiopulmonary resuscitation and called a code blue, resulting in resuscitative efforts that continued for around twenty minutes. In discussion with the hospital ethicist, senior nurses justified these actions, mainly citing disciplinary and medicolegal concerns. We argue that moral harms arise from CPR performed on a corpse and that legal concerns about failing to perform it are unfounded. We contend that such efforts are an unintended consequence of managerialist policies mandating do-not-resuscitate orders and advance care plans and of defensive practices that can value the interests of institutions and practitioners over those of patients. Health management teaching should include managerialism and its pitfalls, while clinician training should prioritize ethical reasoning and legal knowledge over defensive practice.